Pengaruh Brand Image Dan Keputusan Pembelian Produk Terhadap Kepuasan Pelanggan Generasi Z Yang Dimediasi Oleh Nilai Pelanggan: Studi Kasus Pada PT. Indomarco Wilayah Kerja Sampang - Adinda Jennifer Pardede; Hartono Hartono; Yoni Evan Pratama; Abdul Halik (Universitas 45 Surabaya, 2025)
Hartono, 2025. The Influence of Brand Image and Product Purchasing Decisions on Generation Z Customer Satisfaction Mediated by Customer Value (Case Study at PT. Indomarco Sampang Region). Doctoral Program, University of 17 August 1945 Surabaya. Based on its approach, this research is included in the type of explanatory research . The research sample was 146 respondents. The objectives of this study were 1) To test and analyze the significant effect of brand image on customer satisfaction of generation Z PT. Indomarco Sampang Region . 2) To test and analyze the significant effect of product purchasing decisions have a significant effect on customer satisfaction of generation Z PT. Indomarco Sampang Region. 3) To test and analyze the significant effect of brand image has a significant effect on customer value of PT. Indomarco Sampang Region. 4) To test and analyze the significant effect of product purchasing decisions on customer value of PT. Indomarco Sampang Region. 5) To test and analyze the significant effect of customer value has a significant effect on customer satisfaction of generation Z PT. Indomarco Sampang Region. 6) To test and analyze the indirect effect of brand image on customer satisfaction of generation Z PT. Indomarco Sampang Region mediated by customer value. 7) To test and analyze the indirect effect of product purchasing decisions on customer satisfaction of generation Z PT. Indomarco Sampang Region mediated by customer value. The research results show that : 1) brand image has a significant positive effect on customer satisfaction of generation Z PT. Indomarco Sampang Region with an original sample value of 0.256 . 2) Product purchasing decisions have a significant positive effect on customer satisfaction of generation Z PT. Indomarco Sampang Region with an original sample value of 0.530 . 3) brand image has a significant positive effect on customer value of PT. Indomarco Sampang Region with an original sample value of 0.428 . 4) product purchasing decisions have a significant positive effect on customer value of PT. Indomarco Sampang Region with an original sample value of 0.431 . 5) customer value has a significant positive effect on customer satisfaction of generation Z of PT. Indomarco Sampang Region with an original sample value of 0.335. 6) brand image has a significant positive effect on customer satisfaction of generation Z of PT. Indomarco Sampang Region mediated by customer value with an original sample value of 0.37 . 7) product purchasing decisions have a significant positive effect on customer satisfaction of generation Z PT. Indomarco Sampang Region which is mediated by customer value with an original sample value of 0.244 .